EFEK SAMPING PEMAKAIAN ALAT KONTRASEPSI HORMONAL PADA AKSEPTOR KB HORMONAL AKTIF DI DESA JATIROWO DAWAR BLANDONG MOJOKERTO - PUJILESTARI, SRI WARDINI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2010)
The side effect is a result of an action or an even that isn’t wanted by someone. Hormone contraception is one of contraceptive method that inside there is esteregon and progesteron. The kinds of contraception are pill, injection and implant. Hormone contraception has some side effects, they are menstrual pattern trouble, white depression, acne, libido changing, and weight excessed changing, hematoma, asphyxia, headace, infection or abses, nausea, confused, cloasma. The aim of this researh identifies the side effect of using hormone contraseption (pill, injection, and implant) to “KB” acceptor of active hormone in Desa Jatirowo Kecamatan Dawar Blandong Kabupaten Mojokerto in year 2006. The design of this research is descriptive by survey method; sample is used by 64 “KB” acceptor of hormone that get side effect rising after one year using it and has stil got side effect in this researching by causative technic sampling. Only one variable in this research is side effect of using hormone contraception to “KB” acceptor actively. Collecting data is done by giving questioner with observation and interview. The result of this research show us that side effect of using injection contraception majority risely is 35,7% of weight excess, side effect of using contracetion pill is 40% of weight excess, and side effect of using contraception implant is 42,9% amenorhea.The conclusion of this research is the side effect of using hormone contraseption majority risely to “KB” acceptor actively in Desa Jatirowo Kecamatan Dawar Blandong tahun 2006 is weight excess. The researcher’s suggestion is improving quality service and getting hormone “KB” program by crossed subsidy to “KB” acceptor actively.Key words: side effect, contraception, hormone